Internal Audit in Public Hospitals: the case of Greece - Grose, Chris; Petsi, Myrto; Kalialakis, Ioannis; Talias, Michael (Oeconomica Jadertina, 2023)
Internal control is of utmost importance for effective corporate governance, particularly in public hospitals aiming for modernization in the Greek framework. Internal audit functions enhance transparency, enforce accountability, and ensure compliance with societal values, bolstering public trust. This study delves into the implementation of internal control in Greek public hospitals, considering factors like size, structure, and operational intricacies. We explore the regulatory framework, procedures, scope, and objectives, while interviewing auditing experts for insights into challenges and opportunities. Findings reveal procedural dominance in current implementation of the Law. Focus on accounting neglects crucial functional departments. The audit committee's role and composition raise independence concerns. Understaffing further hampers operations. A significant weakness appears in the independence of the audit. Internal auditors report to the hospital administrator and participate in the audit committee. The appointment and remuneration of auditors is not based on the auditor's competence and suitability, but on a cost basis. The question therefore arises as to whether the auditor performs the duties objectively and impartially in accordance with the International Institute of Internal Auditors' standards. Furthermore, regarding the research question on the role of the internal auditor and the treatment by auditees, there has been a significant improvement as evident by the respondents’ answers.
Keywords: Internal Audit, Public Sector, Greek Public Hospitals, Regulatory Framework, Governance Practices